2017
DOI: 10.20944/preprints201704.0177.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical and Experimental Studies of a Switched Inertance Hydraulic System in a Four-Port High-Speed Switching Valve Configuration  

Abstract: Abstract:The switched inertance hydraulic system (SIHS) is a novel high-bandwidth and energyefficient digital device which can adjust or control flow and pressure by a means that does not rely on throttling the flow and dissipation of power. An SIHS can provide an efficient step-up or stepdown of pressure or flow rate by using a digital control signal. In this article, analytical models of an SIHS in a four-port high-speed switching valve configuration are proposed, and the system dynamics and performance are … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The contribution of Pan et al [6] relates to the development of efficient digital hydraulic systems. In particular, they present a study on a switched inertance hydraulic system, which is a novel high-bandwidth and energy efficient digital device which can adjust or control flow and pressure by a means that does not rely on throttling the flow and dissipation of power.…”
Section: Fluid Power Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of Pan et al [6] relates to the development of efficient digital hydraulic systems. In particular, they present a study on a switched inertance hydraulic system, which is a novel high-bandwidth and energy efficient digital device which can adjust or control flow and pressure by a means that does not rely on throttling the flow and dissipation of power.…”
Section: Fluid Power Systemsmentioning
confidence: 99%
“…New approaches for the analysis, modeling, and design of hydraulic and pneumatic components This book contains the successful invited submissions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] to the Special Issue.…”
mentioning
confidence: 99%
“…where twave is the wave propagation time = 2 ⁄ , c is the speed of sound and L is the tube length [8].…”
Section: Enhanced Analytical Model Of Sihsmentioning
confidence: 99%
“…To achieve bi-direction control ability, the four-port SIHS is introduced, as shown in Figure 2, where two inertance tubes and accumulators were used in the system, providing real four-quadrant operation and seamless changes in direction, such as four-port modulating valves. The threeport and four-port SIHS have been investigated analytically and experimentally at the Centre for Power Transmission and Motion Control at the University of Bath [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ren and Ruan (2016) studied vibration waveforms excited by an electro-hydraulic exciter with a two-dimensional rotary valve theoretically and experimentally. Pan et al (2015, 2017) reported on experimental investigations of a switched inertance hydraulic system with a high-speed rotary valve, which is designed to control the flow and pressure of a hydraulic supply. Liu et al (2016, 2017) designed a rotary valve for application to high energy and variable-frequency vibration condition.…”
Section: Introductionmentioning
confidence: 99%